Perlindungan Hak Pekerja dalam Kepailitan Perusahaan - Mia Lestari (JURNAL HAK : Kajian Ilmu Hukum, Administrasi Negara, dan Komunikasi, 2025)
Corporate bankruptcy raises legal issues related to the fulfillment of workers' rights, particularly because, in practice, workers are often in a weak position in the bankruptcy estate settlement process. Although laws and regulations regulate workers' status as preferred creditors, gaps remain between legal norms and their implementation, particularly when conflicts of interest arise with secured creditors or other creditors. This situation demonstrates a gap between normative guarantees of legal protection and the reality of implementation on the ground. This study aims to analyze the forms of legal protection for workers' rights in corporate bankruptcy and to examine workers' legal standing in the distribution of bankruptcy assets. The method used is normative legal research, using a statutory and conceptual approach to examine relevant legal principles, principles, and provisions. The results indicate that, normatively, workers have certain priorities regarding the payment of wages and other rights. However, in practice, legal and technical obstacles remain that have the potential to reduce the effectiveness of this protection.Therefore, consistent interpretation and affirmation of norms are necessary to ensure certainty and fairness for workers in bankruptcy proceedings. This article contributes to strengthening the argument regarding the importance of optimizing legal protection for workers as preferred creditors in the Indonesian bankruptcy legal system.